The Adoption of AI in Public Administration: From Technicality to Competitive Advantage and Public Trust - Brito da Justa Neves, Juliano; da Silva Romão, Ana Lúcia (Revista del CLAD Reforma y Democracia, 2025)
The study of artificial intelligence (AI) began in 1950, but only in the second decade of the 21st century that specific equipment for its processing emerged. Initially, the adoption of AI solutions was influenced by technical factors, such as the complexity of algorithms and the availability of data. However, the scenario changed with the launch of generative AI ChatGPT in 2022. Since then, the pursuit of competitive advantage and the need for modernization have become the main motivators for the adoption of AI in public and private institutions. The rapid popularization of AI has led to a widespread effort to stand out. However, the increased use of AI has raised concerns, especially regarding trust in these technologies, due to the risks of unexpected performance that can harm the image and results of organizations. For public administrations, this issue is critical, as failures in AI solutions can impact the entire society and are not easily correctable. This work evaluates the factors that influence the adoption of AI in public administrations, from initial technical criteria to the current concern with AI trust and regulation, aiming to provide a comprehensive view of the challenges and propose future directions for research and practice.